Kubernetes and Cloud Native Associate (KCNA), - Vugt, Sander van (LiveLessons (Boston, Massachusetts), 2022)
5 Hours of Video Instruction 5 hours of deep-dive training to teach you the concepts and skills needed to pass the Kubernetes and Cloud Native Associate (KCNA) exam. Overview Kubernetes and Cloud Native Associate (KCNA) Complete Video Course is an 8-hour video training course to help you successfully prepare you for the KCNA exam. It will also help you gain a solid understanding of Kubernetes topics and concepts to help you get started with Kubernetes and Cloud Native computing. Expert trainer Sander van Vugt provides a hands-on approach to learning by going deeper into exam topics and concepts using real-world labs and demos. Each lesson in the course ends with a lab exercise along with a practice question review so you can practice your skills and test your knowledge. There is no better place to start your Cloud Native with Kubernetes journey than by studying for the Kubernetes and Cloud Native Associate (KCNA) exam. KCNA is a pre-professional certification created by Cloud Native. It was designed to help candidates advance their Kubernetes skills to the professional level. This Cloud Native certification covers the foundational knowledge and skills needed to start working with Kubernetes in a Cloud Native environment. Sander van Vugt has carefully structured this 11-lesson course to focus on concepts, practices, and solutions used in cloud native environments. The course begins with an exploration of the cloud native certification program before moving onto a look at Cloud Native technologies and solutions. You will then get real-world knowledge on running and orchestrating containers. The next step is a deep dive into Kubernetes--understanding, running, scaling, and finally integrating applications in Cloud Native. The course ends with hands-on lessons showing how to run and deliver applications while using observability solutions. Topics include Module 1: Cloud Native Certifications Module 2: Cloud Native Technologies and Solutions Module 3: Using Containers Module 4: Using Kubernetes Module 5: Running Applications in Cloud Native About the Instructor Sander van Vugt has many years of experience working with, writing about, and teaching Linux and Open-Source topics. He is the author of the best-selling Red Hat RHCSA and RHCE Cert Guides as well as a number of other titles on Kubernetes (including CKAD and CKA), Ansible, Containers, Bash, Microservices, and more. Sander also works as a Linux and DevOps instructor, teaching onsite and online classes for customers around the world. Skill Level Beginner to Intermediate Learn How To Successfully prepare for the KCNA exam Work in cloud native environments, with cloud native technologies and solutions Use containers and container orchestration Run Kubernetes, Minikube environment, and run applications in Kubernetes Run applications in a cloud native environment Who Should Take This Course Anyone looking to pass the KCNA exam Anyone interested in learning Kubernetes and its basic concepts Anyone interested in working with cloud native technologies About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.